Flexible congestion control using fuzzy logic for Wireless Sensor Networks - Arora, M; Upadhyaya, S; Kashyap, N (International Journal of Computer Sciences and Engineering, 2025)
In WSNs, congestion seems to be an unpredictable stage caused by the packets collision and the overloaded network. The main reason of overloading is the neighboring nodes. In large networks, mainly neighbor nodes behave smartly to grasp the large amount of bandwidth in advance for packet transmission. The affect of low bandwidth causes the problem of packet delay and dropping rate. Both network and transport layer share the responsibility to control the congestion. To achieve these objectives, Flexible congestion control scheme (FCCFA) is proposed. FCCFA uses the closed loop congestion control technique to control the traffic rate accordingly by using three parameters. The Type-2 Fuzzy Logic System is used to estimates the adjustment rate to handle the uncertainty of data. Implicit notification system is used to notify the immediate nodes without wasting any energy. The simulated results give the proof of our promises and improvements.